2009
DOI: 10.1002/cbdv.200800182
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Diselenide‐Linked Porphyrin Dimers under Phase‐Transfer Catalysis Condition and Their Interactions with DNA

Abstract: Novel diselenide-linked porphyrin dimers were synthesized under phase-transfer catalysis conditions. The targeted compounds were characterized by (1)H-NMR, high-resolution mass spectrometry, UV/VIS and fluorescence spectroscopies, redox-potential measurements, and elemental analysis. The interaction of the title compounds with DNA was studied using UV/VIS, fluorescence, and circular dichroism (CD) spectroscopies. The relative rates of singlet-oxygen production from the diselenide-linked porphyrin dimers upon p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…37,38 Selenium powder (2.37 g, 30 mmol) in 10 mL of water was added to a three-necked flask under a nitrogen atmosphere. NaBH 4 (2.27 g, 60 mmol) dissolved in 25 mL of cold H 2 O was syringed dropwise into the selenium suspension.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 Selenium powder (2.37 g, 30 mmol) in 10 mL of water was added to a three-necked flask under a nitrogen atmosphere. NaBH 4 (2.27 g, 60 mmol) dissolved in 25 mL of cold H 2 O was syringed dropwise into the selenium suspension.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…27,29,[34][35][36][37] After it was found that low molecular weight oligoethylenimine (OEI) cross-linked by dithiobis (succinimidylpropionate) or dimethyl ⋅ 3,3′-dithiobispropionimidate ⋅ 2HCl achieved highly efficient transfection in vitro and had lower cytotoxicity, 34 much research attention has been focused on modification of different disulfide bonds containing linkers [27][28][29]35 and effect of the molecular weight of cross-linked OEI. 35 Inspired by the success of disulfide bonds, the selenium (Se) element listed in the same family as sulfur (S) in the periodic table of elements has attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only porphyrins replaced with alkylselenium groups have been synthesized, but no alkylselenium phthalocyanines have been reported. 5,[11][12][13][14][15] Based on these results, further studies have been initiated to investigate the synthesis and spectroscopic properties of a novel selenium derivatized zinc(II) phthalocyanine complex to evaluate its properties as a potential photosensitizer for clinical purposes.…”
Section: Introductionmentioning
confidence: 99%